Analysis of Sharia Stock Valuation Using The FCFE And Relative Valuation Methods Sector Listed on The Sharia Securities List - Hanafi Hamonangan, Muhammad; Nurlaila; Batubara, Maryam (Dinasti Publisher, 2024)
The objective of this study is to analyze the intrinsic value of sharia stocks in the property sector listed on the Sharia Securities List (DES), utilizing two distinct valuation methodologies: free cash flow to equity (FCFE) and relative valuation. The stocks selected for analysis include PT Metropolitan Kentjana Tbk (MKPI), PT Mega Manunggal Property Tbk (MMLP), and PT Pollux Properties Indonesia Tbk (POLL). In this study, the free cash flow to equity (FCFE) method was employed to ascertain the intrinsic value of the shares. This was achieved through the consideration of free cash flow, which was subsequently deducted to account for expenses pertaining to working capital and investment. In contrast, the relative valuation method involved the comparison of the intrinsic value of the shares with financial ratios such as the price-to-earnings ratio (PER) and the price-to-book value (PBV). The aforementioned approach was informed by a fundamental analysis, which involved the examination of macroeconomic conditions, industry conditions, and company conditions. The data was obtained from property companies listed on the Indonesia Sharia Stock Index (ISSI) for the period 2019-2022. The results indicated that the intrinsic value of MKPI stock, as determined by the FCFE method, was Rp. 24,134. This value suggests that the stock is overvalued, given that the market price was Rp. 27,200. The PER method yielded the following results: The intrinsic value of the stock is Rp. 59,461, indicating that it is undervalued. The PBV method yields an intrinsic value of IDR 7,515, indicating that the stock is overvalued. The MMLP Shares are valued using the FCFE method, which yields an intrinsic value of IDR 4,857, indicating that the stock is undervalued as the market price is IDR 298. The PER method yields an intrinsic value of IDR 686, indicating that the stock is undervalued. The intrinsic value of the stock is IDR 893, indicating that it is undervalued. The PBV method yields an intrinsic value of IDR 686, also indicating undervaluation. The POLL stock is undervalued according to the FCFE method, with an intrinsic value of IDR 251. This is due to the market price of IDR 147. Finally, the PER method yields an intrinsic value of IDR 109, indicating that the stock is undervalued. The intrinsic value of IDR 109 indicates that the stock is undervalued. The PBV method yields an intrinsic value of IDR 214, which also indicates undervaluation. In conclusion, the FCFE and Relative Valuation methods can be used to determine the fairness of Islamic stock prices in the property sector. The data was obtained from property companies listed on the Indonesia Sharia Stock Index (ISSI) for the period 2019-2022. The results indicated that the intrinsic value of MKPI stock, as determined by the FCFE method, was Rp. 24,134. This value suggests that the stock is overvalued, given that the market price was Rp. 27,200. The PER method yielded the following results: